2007
DOI: 10.1007/s11837-007-0085-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of additives to SnAgCu alloys on microstructure and drop impact reliability of solder joints

Abstract: Research Summary Lead-Free SolderThe impact reliability of solder joints in electronic packages is critical to the lifetime of electronic products, especially those portable devices using area array packages such as ball-grid array (BGA) and chip-scale packages (CSP). Currently, SnAgCu (SAC) solders are most widely used for lead-free applications. However, BGA and CSP solder joints using SAC alloys are fragile and prone to premature interfacial failure, especially under shock loading. To further enhance impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(45 citation statements)
references
References 4 publications
2
43
0
Order By: Relevance
“…In solder joints specifically, the microstructure can affect the performance including the fatigue life during thermal cycling [135], the tolerance to drop impacts [136] and the resistance to electromigration [137]. Since the mechanism by which reinforcement particle additions cause a refinement in the the intermetallics present in are unclear, this study focuses on the microstructure formation in reinforced solder joints.…”
Section: Summary and Remarksmentioning
confidence: 99%
“…In solder joints specifically, the microstructure can affect the performance including the fatigue life during thermal cycling [135], the tolerance to drop impacts [136] and the resistance to electromigration [137]. Since the mechanism by which reinforcement particle additions cause a refinement in the the intermetallics present in are unclear, this study focuses on the microstructure formation in reinforced solder joints.…”
Section: Summary and Remarksmentioning
confidence: 99%
“…A variety of lead-free solder alloys have been investigated, such as SnAg, SnCu, SnAgCu and so on. These alloys have good solderability, thermal fatigue reliability and compatibility with the components and circuits [5]. Hence, they are recommended to be the most potential alternatives for SnPb solder [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [5,12] reported that the Mn/Ce doped Sn1.0Ag0.5Cu alloys achieved a homogeneous microstructure, high strength in drop tests and high reliability in dynamic bending tests. The Sn1.0Ag0.5Cu ?…”
Section: Introductionmentioning
confidence: 99%
“…The effects of reinforcement on the microstructural, mechanical, thermal and electrical properties of the resultant composite solder have been extensively investigated by several researchers [9][10][11][12]. One of the choices of reinforcement is carbon nanotubes (CNTs).…”
Section: Introductionmentioning
confidence: 99%